Mathematics and Engineering - Li, Mingheng; Sun, Hui (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a compilation of works covering applied mathematical methods and their applications in complex engineering problems. The methods covered in this book include modeling and simulation, computation, analysis, control, optimization, data science, and machine learning. The engineering application topics include but are not limited to environmental engineering, cybersecurity, transportation, agriculture, smart grid, and next-generation manufacturing.